Neoliberal Universities, Patriarchies, Masculinities, and Myself: Transnational-personal Reflections on and from the Global North - Jeff Hearn (Gender a Výzkum)
This article reflects on working in eight universities in Finland, Sweden, and the UK, along with many transnational research projects. These are analysed within the framework of what might be called neoliberal universities, neoliberal trans(national)patriarchies, and neoliberal masculinities. Importantly, these are reflections from the global North, being transnationally located there, rather than glossed as ‘global’ or simply assumed as nationally contextualised. This discussion is located within the burgeoning literature on neoliberalism, and then proceeds to examine, first, experiences in the UK, before those in Finland and Sweden. The final section focuses on the transnationalisation of these neoliberal processes in academia – for example, through transnational research development, projectisation of research, and language use, performance and performativity. In such ways multiple connections are drawn between the greater organisational ‘autonomy’ of universities, contradictions of transnationalisations of academia, and the construction of ‘autonomous’ individual(ist) academics.